2019
DOI: 10.1039/c9ce00668k
|View full text |Cite
|
Sign up to set email alerts
|

Doping of aluminum (Al) into copper sulfide (CuS) nanocrystals enhanced their solar spectral selectivity

Abstract: Al-CuS/PVA film possessed low NIR transmittance and high visible light transmittance. CuS nanocrystals doping Al significantly enhance their solar spectral selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…This iodine doping can occur because of the higher electronegativity of iodine compared to that of Cu, [18] similar doping mechanism with previously reported metal-ion-doped CuS. [19][20][21][22][23][24][25][26] The CuS electrode, which is covellite and nanosheet structure, was synthesized based on a room-temperature sulfur activation method which is reported at our previous article. [27] The thickness of CuS was controlled to be 20 % 40 nm which is optimized conditions with a low sheet resistance (Figure 1b).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This iodine doping can occur because of the higher electronegativity of iodine compared to that of Cu, [18] similar doping mechanism with previously reported metal-ion-doped CuS. [19][20][21][22][23][24][25][26] The CuS electrode, which is covellite and nanosheet structure, was synthesized based on a room-temperature sulfur activation method which is reported at our previous article. [27] The thickness of CuS was controlled to be 20 % 40 nm which is optimized conditions with a low sheet resistance (Figure 1b).…”
Section: Resultssupporting
confidence: 73%
“…These enhanced properties can be attributed to the induced iodine molecules that are adsorbed to the sulfur vacancy sites in CuS, resulting in the increase of the hole concentration. [ 21 , 32 ] Such changes in the electrical properties of the CuS nanosheet upon the iodine doping indicate that the iodine is an effective in modulating the charge carrier densities of CuS electrode and leads to more metallic electrical properties (Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the composition, surface morphology, and crystalline phase of CuS nanoparticles influence their photocatalytic efficiencies [ 21 , 22 ]. These properties are affected by the synthetic methods used for the preparation of CuS nanoparticles, which includes solvothermal [ 23 ], hydrothermal [ 24 ], sol-gel [ 25 ], micro-emulsion [ 26 ], microwave [ 27 ], sonochemical [ 28 ], electrospinning [ 29 ] and single-source precursors [ 30 , 31 ]. The use of a single-source precursor to prepare CuS nanoparticles has been reported to give high-quality nanoparticles due to the metal-sulfur bond in the precursors [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…CuS nanomaterials are endowed with the optical band gap energy ranging from 1.2 to 2.5 eV, particularly with an enhanced light absorption in the NIR region by means of the localized surface plasmon resonances. [39,40] Likewise, CDs also possess a tunable bandgap due to the quantum size effect and they have superior photoinduced electron transfer and electron reservoir properties. [15][16][17][41][42][43][44] After integration of them into a heterostructure, the formed interfaces not only create the new absorption bands for improving sunlight harvesting (see Figure 2a), but also induce internal electric fields to facilitate charge separation and migration (see Figure 4c,d).…”
Section: Resultsmentioning
confidence: 99%